Racial differences in body-mass indices for men imprisoned in 19th century US prisons: A multinomial approach - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2010)
Little research has been done on the body mass index values of 19th century US African-Americans and whites. This paper uses 19th century US prison records to demonstrate that although modern BMIs have increased in the 20th century, 19th century black and white BMIs were distributed symmetrically; neither underweight nor obese individuals were common. Throughout the 19th century, black and white BMI values declined. Farmers were consistently heavier than non-farmers, and blacks in Upper South had lower BMI values than their counterparts in other US regions.
Keywords: I10; I12; I30; J10; J15; 330; body mass index; 19th century American health; racial disparity; Gesundheit; Übergewicht; Anthropologie; Weiße; Farbige Bevölkerung; Vergleich; Straftäter; Teilstaat; USA